2005
DOI: 10.1063/1.1857653
|View full text |Cite
|
Sign up to set email alerts
|

Large energy absorption in Ni–Mn–Ga/polymer composites

Abstract: In recent years Ni-Mn-Ga has attracted considerable attention as a new kind of actuator material. Off-stoichiometric single crystals of Ni 2 MnGa can regularly exhibit 6% strain in tetragonal martensites and orthorhombic martensites have shown up to 10% strain when subjected to a magnetic field. These crystals are brittle and the production of single crystals can be quite costly. Terfenol-D, a commercially available giant-magnetostrictive material, suffers from some of the same drawbacks. It was found that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
54
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 20 publications
6
54
0
Order By: Relevance
“…Recently, smart composites consisting of Ni-MnGa alloy powders in polymer matrix have raised some interests because of their several advantages over bulk materials for practical applications, such as low cost, good formability, and low AC eddycurrent losses. It has been found that FSMA/polymer composites exhibit good shape recovery [7] and large mechanical energy absorption [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, smart composites consisting of Ni-MnGa alloy powders in polymer matrix have raised some interests because of their several advantages over bulk materials for practical applications, such as low cost, good formability, and low AC eddycurrent losses. It has been found that FSMA/polymer composites exhibit good shape recovery [7] and large mechanical energy absorption [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Single crystalline particles embedded in a stiffness-matched polymer matrix allow overcoming the disadvantages. A thin polymer film between the single crystalline particles allows the particles to strain und reduces s twin .…”
mentioning
confidence: 99%
“…Composites with a stiff polymer matrix can dissipate a large amount of input energy by stress induced twin boundary motion within the particles and therefore can be used as dampers. [7,8] The application as actuators requires magnetically induced twin boundary motion and thus a polymer matrix with a lower stiffness is necessary. Alignment of the Ni-Mn-Ga particles with their easy magnetisation axis parallel to each other can be achieved by applying a magnetic field during curing of polymer matrix.…”
mentioning
confidence: 99%
“…The composites are made by 24% volume of Ni-Mn-Ga powder where the volume percentage is optimized from the previous works (Jorge Feuchtwanger et al 2005). Although, 20% Ni-Mn-Ga in PU, 24% Ni-Mn-Ga in PU, 30% Ni-Mn-Ga in PU and 36% Ni-Mn-Ga in PU composites have been prepared for our investigations, only 24% Ni-Mn-Ga in PU has been optimized for this work.…”
Section: Methodsmentioning
confidence: 99%